Acyclic Aldehydo Sugars: 1,3-dimethyl-4,5-diamino Uracil as Recoverable Carbonyl Protecting Group - Fuentes-Ríos, David; Doña-Flores, Manuel; López-Romero, Juan Manuel; Rico, Rodrigo (Bentham Science, 2024)
1,3-dimethyl-4,5-diaminouracil has been used as an efficient protecting group for the car- bonyl moiety in sugars by the formation of the imine group. The protection reaction is carried out under mild conditions, the yields are quantitative in most of the cases, and the protecting group is completely recovered and reused. After per-acetylation, deprotection is accomplished at room temperature with aqueous formic acid to produce acyclic acetylated sugars in good global yield.
Keywords: Química orgánica; Azúcar - Aspectos moleculares; Acyclic aldehydo sugars; Carbonyl; Uracil; Thioacetals; Butyllithium; Organic synthesis